Looking From a Window: A Critical Analysis of the T’boli’s Worldview Through their Oral Traditions - Casinto, Carlo Domingo (International Journal of Language and Literary Studies, 2022)
This study analyses a collective worldview through the values embodied in the oral traditions of the T’boli, an indigenous tribe in Lake Sebu, the Philippines. Utilising ethnographic method, data collection is made primarily through informants’ in-depth interview and literary criticism of the oral traditions. The study records, transcribes, translates, codes and classifies the T’boli’s oral traditions according to their genre. Framed under Carl Jung’s Archetypal Criticism’s perspective, it identifies T’boli’s religious, human, and cultural values in the mythical characters and in the recurring motifs and themes of their oral traditions. The prominent motifs in T’boli’s oral traditions are the controlling imageries of a deity and a body of water. The recurring didactic teachings in the themes are devotion, altruism, and deference. The embodied values are faithfulness, generosity and respect and obedience to authority. These values shape the T’boli’s worldview in terms of their cultural and religious practices and traditions.